The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1017/dsj.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

Improving human understanding and design of complex multi-level systems with animation and parametric relationship supports

Abstract: (2015). Improving human understanding and design of complex multi-level systems with animation and parametric relationship supports. Design Science, 1, e3 doi:10.1017/dsj. 2015 AbstractComplex systems are challenging to design, particularly when they contain multi-level organizations with non-obvious relationships among design components. Here, we investigate engineering students' capacity to search for optimal nanoscale biosystem designs with stochastic component and system behaviors. The study aims to chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…In the simulation, each myosin's structure was designable and linked to behaviors that influence design performance [15]. Human designers interacting with the agent-based simulation gained understanding of the system that improved their ability to search a parametric design space [18]. These studies offer validation for using a parametric design representation for the human-in-the-loop approach.…”
Section: Cognitive Processes For Complex Systems Designmentioning
confidence: 99%
See 2 more Smart Citations
“…In the simulation, each myosin's structure was designable and linked to behaviors that influence design performance [15]. Human designers interacting with the agent-based simulation gained understanding of the system that improved their ability to search a parametric design space [18]. These studies offer validation for using a parametric design representation for the human-in-the-loop approach.…”
Section: Cognitive Processes For Complex Systems Designmentioning
confidence: 99%
“…Once computational biological models are validated, they may be utilized to evaluate new system configurations that are representative of designs. In our past work, agent-based myosin models were validated with empirical data [16] and provided a means for evaluation in engineering optimization tasks representative of myosin technologies [18]. Since these tasks represent a variety of technologies, an interesting design problem emerges when considering the best set of myosins for use in all technologies, such as selecting myosins from a design catalog.…”
Section: Cognitive Processes For Complex Systems Designmentioning
confidence: 99%
See 1 more Smart Citation
“…A human designer may then steer computational processes with a "human-in-the-loop" design approach by making highlevel decisions that guide the computational processes towards more beneficial solutions . In this framework, a human designer could potentially steer computational processes based on knowledge of multilevel parameter interactions that influence qualitatively distinct emergent system behaviours (Egan et al 2015c) and could potentially be difficult to formalize computationally. Empirical research studies can play a role in scientifically determining the most effective way to interface human and computational decision-making processes for solving such design problems.…”
Section: Human and Computational Design Approachesmentioning
confidence: 99%
“…One of our recent human participant experiments demonstrated that human understanding of qualitative behaviours across complex system scales improves human design decision-making performance (Egan et al 2015c). However, a precise cognitive mechanism for how designers translate such understanding towards better design decision-making was not identified.…”
Section: Potential Cognitive Phenomenon To Investigatementioning
confidence: 99%